Categorização e multifuncionalidade: léxico e gramática - Neves, Maria Helena de Moura [UNESP] (My University, 2010)
Linguistic studies have always been oriented by the categorization of language, despite the obvious existing and undeniable fuzziness of the borders between linguistic categories. This statement specifically applies to the categories established as result of study of the grammar of languages, but it also unavoidably implies the classification of the lexicon, and, through the latter the organization of dictionaries, both in terms of macro and microstructure. Thus, the concept of categorization (as well as prototype) is particularly importante to this dicussion.

Os estudos linguísticos sempre se pautaram por um estabeleciemnto de categorias para a língua, apesar da evidente diluição de fronteiras que existe e que deve ser admitida. A indicação se refere especificamente às categorias estabelecidas nos estudos gramaticais das línguas, mas fica inevitavelmente implicada a classificação do léxico, e, por essa via, a organização de dicionários, tanto na macroestrutura como na microestrutura. É particularmente importantes nessa discussão o conceito de categorização (e prototipia).
Keywords: Lexicon; Grammar; Dictionary; Categorization; Léxico; Gramática; Dicionário; Categorização